Equilibrium real interest rates, secular stagnation, and the financial cycle: Empirical evidence for euro-area member countries - Ansgar Belke; Jens Klose (Research On Money in the Economy (ROME), 2018)
Is the Euro area as a whole, or are individual Euro-area member countries facing a period of sustained lower economic growth, a phenomenon known as secular stagnation? We tackle this question by estimating equilibrium real interest rates and comparing them to actual real rates. Since the financial crisis has altered the degree of leverage in several European economies, we expand our model to incorporate the financial cycle. We estimate the model for the Euro area as a whole and for nine Euro-area member countries. Incorporating the financial cycle changes the estimated equilibrium real interest rates: For some of Euro-area member countries, estimates of the equilibrium real interest rate are substantially higher than the standard estimates. In other cases, including our estimates for the Euro area as a whole, the estimated equilibrium real rates are slightly lower than without taking the financial cycle into account but are still higher than the actual rates. This indicates that real monetary policy rates were set even more systematically and consistently below (or not as far above) the natural real rate. Comparing the sequence of actual and equilibrium real rates, only Belgium, France, and Greece are likely to face a period of secular stagnation.
Keywords: E43; F45; C32; 330; equilibrium real interest rate; Euro area; financial cycle; heterogeneity; monetary policy; secular stagnation